The Quality of Unit Services Outpatient towards Satisfaction: A Literature Review - Heris Dwityo Pelawinta; Ermi G; Sri Lestari Ramadhani Nasution (PSPP JOURNALS, 2021)
This article discusses about quality of outcoming unit services on patient satisfaction. The quality of care offered to patients is likely to suffer as a result of bad human relationships, poor technological competence, and poor efficiency in health services. Patients' satisfaction is a key indicator of good hospital procedures and a barometer for the quality of care received. If a hospital's patients are dissatisfied, it will have a negative impact on its bottom line. Many factors influence patient satisfaction in hospitals or other health care organizations. There are several techniques to gauge customer satisfaction.